Escheriosome: A potential antigen carrier - Chavda, Vivek P. (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2016)
Escheriosomes are one kind of liposomes grafted from polar lipids extracted from Escherichia coli. These vesicular form elicit high cytotoxic T lymphocyte (CTL) responses. Escheriosomes have shown to deliver their entrapped molecules right into the cytosol of the APCs (Antigen Presenting Cells) that leads to the processing of entrapped antigen via endocytic pathway leading to the antigen presentation by MHC Class I mode. Expression via MHC class I molecules results in CD8+ T cell activation. Escheriosomes may function as a novel immunoadjuvants and emerge as an effective tool for generating protective immunity. It proves to be attractive niche for the scientist in the delivery of vaccine. This review is grafted to highlight its potential as antigenic carrier along with its characterization.